2016
DOI: 10.1038/nmeth.3929
|View full text |Cite
|
Sign up to set email alerts
|

Contrast agents for molecular photoacoustic imaging

Abstract: Photoacoustic imaging (PAI) is an emerging tool that bridges the traditional depth limits of ballistic optical imaging and the resolution limits of diffuse optical imaging. Using the acoustic waves generated in response to the absorption of pulsed laser light, it provides noninvasive images of absorbed optical energy density at depths of several centimeters with a resolution of ∼100 μm. This versatile and scalable imaging modality has now shown potential for molecular imaging, which enables visualization of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
984
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,105 publications
(993 citation statements)
references
References 144 publications
6
984
0
3
Order By: Relevance
“…Targeting this nanostructure to a specific biochemical process would enable highly efficient photoacoustic molecular imaging with translational potential. 32 In conclusion, we have shown that the process of fluorescence quenching can be exploited to create photoacoustic rulers, which could, in the future, be applied for studies of molecular interactions at depth in living subjects.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Targeting this nanostructure to a specific biochemical process would enable highly efficient photoacoustic molecular imaging with translational potential. 32 In conclusion, we have shown that the process of fluorescence quenching can be exploited to create photoacoustic rulers, which could, in the future, be applied for studies of molecular interactions at depth in living subjects.…”
Section: Discussionmentioning
confidence: 86%
“…31 Here, we report a systematic study of PAT molecular rulers using DNA nanostructures to precisely tune the distance between a fluorophore and quencher pair suitable for in vivo imaging in the near-infrared (NIR) optical window. 32 We assess the absorbance, fluorescence and photoacoustic properties of our DNA nanostructures as a function of fluorophore-quencher separation distance. Importantly, we demonstrate experimentally the potential of PAT for performing nanoscale distance measurements at depth in tissue mimicking phantoms and also highlight the utility of DNA nanostructures to enhance the photoacoustic signal generation capabilities of small molecule fluorescent dyes.…”
Section: Photoacoustic (Pa) Tomography (Pat) Is Emerging As An In Vivmentioning
confidence: 99%
“…PAI provides activatable molecular contrast, which can then be superimposed on an anatomical background provided by traditional US using macroscopic or microscopic imaging configurations 95 . Some endogenous biological molecules naturally exhibit sufficient photoacoustic conversion efficiency necessary for PAI contrast (in particular haemoglobin, for probing hypoxia 96 or angiogenesis 97 ), and likewise do exogenous fluorescent dyes used in traditional molecularly targeted OI strategies 98 . However, the customisable structure and composition of nanomaterials have motivated their status as perhaps the most 'engineerable' platforms for PAI, particularly for integrating photoacoustic imaging with MRI, OI and therapeutic strategies.…”
Section: Paimentioning
confidence: 99%
“…Photoacoustic imaging-using a short laser pulse to generate ultrasound transients from optical absorbers-improves image contrast while maintaining many advantages of ultrasound imaging. Introduction of targeted contrast agents for photoacoustic imaging provides information about molecular composition of in vivo tissues [13,14]. Imaging of function is a particular strength of photoacoustic techniquesmeasurements of hemoglobin oxygen saturation (sO 2 ) been demonstrated in phantoms [15] and preclinical models [16][17][18].…”
Section: Introductionmentioning
confidence: 99%